2014
DOI: 10.1111/jne.12206
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol and Diet Modulate Energy Homeostasis and Hypothalamic Neurogenesis in the Adult Female Mouse

Abstract: Leptin and oestradiol have overlapping functions in energy homeostasis and fertility, and receptors for these hormones are localised in the same hypothalamic regions. Although, historically, it was assumed that mammalian adult neurogenesis was confined to the olfactory bulbs and the hippocampus, recent research has found new neurones in the male rodent hypothalamus. Furthermore, some of these new neurones are leptin-sensitive and affected by diet. In the present study, we tested the hypothesis that diet and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 116 publications
(179 reference statements)
4
58
0
Order By: Relevance
“…Leptin receptors are co-localized with ERs in the arcuate nucleus of the hypothalamus indicating a direct mechanism by which E2 increases leptin sensitivity [134]. More recently it was shown in female rodents fed a CDD that E2 decreases diet-induced hypothalamic neurogenesis of leptin-sensitive neurons in the arcuate [135]. A similar study showed that E2 administration in ovariectomized mice normalizes the decreased insulin sensitivity associated with four weeks of HFD exposure [136].…”
Section: Possible Mechanisms By Which Stress Exposure Alters E2’s Actmentioning
confidence: 99%
“…Leptin receptors are co-localized with ERs in the arcuate nucleus of the hypothalamus indicating a direct mechanism by which E2 increases leptin sensitivity [134]. More recently it was shown in female rodents fed a CDD that E2 decreases diet-induced hypothalamic neurogenesis of leptin-sensitive neurons in the arcuate [135]. A similar study showed that E2 administration in ovariectomized mice normalizes the decreased insulin sensitivity associated with four weeks of HFD exposure [136].…”
Section: Possible Mechanisms By Which Stress Exposure Alters E2’s Actmentioning
confidence: 99%
“…This finding suggests a degree of plasticity that is evolutionarily conserved and likely extends to humans as well (Batailler et al 2013;Dahiya et al 2011;Noguiera et al 2014). Both juvenile and adult mammalian hypothalamus exhibit ongoing neurogenesis that can be regulated by growth and differentiation factors (Pencea et al 2001;Xu et al 2005;Kokoeva et al 2005;Perez-Martin et al 2010;Robins et al 2013b), diet Li et al 2012;McNay et al 2012;Gouaze et al 2013;Bless et al 2014), antidepressants (Sachs and Caron 2014), exercise (Matsuzaki et al 2015), and hormones (Ahmed et al 2008;Bless et al 2014). Although these studies generally agree that levels of constitutive hypothalamic neurogenesis are much lower than those seen in well-characterized neurogenic zones in the adult brain, such as the subventricular zone of the lateral ventricles or the subgranular zone of the lateral hypothalamus , they often report differing effects of extrinsic factors on cell proliferation and neurogenesis in hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while multiple groups have reported that long-term administration of HFD inhibits cell proliferation and neurogenesis in hypothalamic parenchyma (Li et al 2012;McNay et al 2012;Gouaze et al 2013;Bless et al 2014), studies investigating acute responses to HFD have reported increased hypothalamic cell proliferation and neurogenesis (Thaler et al 2012;Gouaze et al 2013). Acute HFD administration has also been reported to rapidly induce hypothalamic inflammation, increasing cytokine signaling (Thaler et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17-estradiol (E2) signaling in the hypothalamus, both through classical estrogen receptors ERs (ERα and ERβ) and membrane-associated ERs, including G protein-coupled estrogen receptor 1 (GPER1), is involved in regulating the transcription and release of gonadotrophin releasing hormone (GnRH) and luteinizing hormone (LH) (Petersen et al 2003). E2 also regulates various neural pathways, such as those involved in sexual receptivity (Micevych and Dominguez 2009) and energy homeostasis (Bless et al 2014).…”
Section: Effects Of E2 And/or Gly On Nr4a1 Expressionmentioning
confidence: 99%